2021
DOI: 10.1039/d1nj01594j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional C3N/blue phosphorene vdW heterostructure for Li, Na and K-ion batteries

Abstract: We investigate a van der Waals heterostructure constructed using BP and C3N and investigate its use as an anode for lithium-, sodium- and potassium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…However, the adsorption characteristic of Na atom on the outer-surface of Blu-Pn has decreased from À1.52 eV for pristine Blu-Pn to À1. 65 with the V Pn -site having the strongest binding energy, which is similar to the case of Na adsorbed over pristine Blu-Pn sheet. Finally, the BC 2 N/Na/Blu-Pn configuration with a binding energy of DE B = À2.03 eV is found to be energetically more stable than the BC 2 N/Blu-Pn/Na and Na/BC 2 N/Blu-Pn configurations by a difference of À0.38 eV (À1.65 eV) and À0.78 eV (À1.25 eV), respectively.…”
Section: Structural Stability and Electronic Properties Of The Bc 2 N...supporting
confidence: 56%
See 2 more Smart Citations
“…However, the adsorption characteristic of Na atom on the outer-surface of Blu-Pn has decreased from À1.52 eV for pristine Blu-Pn to À1. 65 with the V Pn -site having the strongest binding energy, which is similar to the case of Na adsorbed over pristine Blu-Pn sheet. Finally, the BC 2 N/Na/Blu-Pn configuration with a binding energy of DE B = À2.03 eV is found to be energetically more stable than the BC 2 N/Blu-Pn/Na and Na/BC 2 N/Blu-Pn configurations by a difference of À0.38 eV (À1.65 eV) and À0.78 eV (À1.25 eV), respectively.…”
Section: Structural Stability and Electronic Properties Of The Bc 2 N...supporting
confidence: 56%
“…A similar tendency has been revealed, for example, in the diffusion of Li in BlueP/G and VS 2 /BlueP systems, 55,62 and the migration of Na in the C 3 N/BP vdW heterostructure. 65 As presented in Fig. 5(c), the diffusion of Na on the outer-surface of BC 2 N is investigated by dividing the whole pathway into three nonequivalent segments, namely, H CN -H BCN , H BCN -H CB , and H CB -H CN , linking the abovementioned possible adsorption sites.…”
Section: Structural Stability and Electronic Properties Of The Bc 2 N...mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural distortion of the cathode material induces significant deterioration, manifesting as increased capacity decay and compromised cycling longevity. Elastic constants are crucial in assessing the material's mechanical stability [40]. The evaluated diagonal component within the elastic constants C 11 and C 22 manifests as 72 and 100 GPa, respectively, thereby corroborating the inherent stability of the system.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 70%
“…For example, Yang et al showed that adding a second layer of lithium ions on top of the C 4 N monolayer resulted in almost the same number of electrons being transferred from the lithium ions to the substrate, while the calculated adsorption energies were still negative. Therefore, despite the fact that some studies have considered multilayer adsorption of various metal ions on the substrates solely based on the negative adsorption energies we took a different approach by focusing on only one-layer adsorption to ensure large charge transfers.…”
Section: Resultsmentioning
confidence: 99%